Existence of solutions of boundary-value problems corresponding to a certain difference equation in a Banach space - Gorodnii, M. F. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
The problem of the existence and uniqueness of solutions is studied for boundary-value difference problems corresponding to a certain linear difference equation in a Banach space.